Barriers and needs in mental healthcare of adults with autism spectrum disorder in Germany: a qualitative study in autistic adults, relatives, and healthcare providers - Sophia Dückert; Petia Gewohn; Hannah König; Daniel Schöttle; Alexander Konnopka; Pascal Rahlff; Frank- Erik; Kai Vogeley; Holger Schulz; Nicole David; Judith Peth (BMC Psychiatry, 2023)
Abstract Background Autism refers to a neurodevelopmental condition with characteristic impairments in social interaction and communication, restrictive and repetitive behaviors, as well as difficulties in sensory information processing and daily living skills. Even though symptoms persist from early childhood throughout the lifespan and often require long-term support, there is a lack of mental health services that sufficiently meet the needs of autistic adults. Previous evidence suggested individual, professional and structural barriers to healthcare for autistic adults. Here, using a peer research approach, we sought to systematically investigate barriers and needs in mental healthcare of autistic adults in Germany at the three relevant levels (individual, professional, structural) and from three relevant perspectives (autistic adults, relatives and healthcare providers), in order to obtain specific recommendations for optimized healthcare. Methods Maximum variation sampling was used to account for the complexity of the research field. Semi-structured, open-ended interviews were conducted with autistic adults (n = 15) and focus groups with relatives/partners (n = 12), and healthcare providers of several professions (n = 15). Data analysis was performed using the codebook approach of thematic analysis. Results Poor mental healthcare of autistic adults in Germany was characterized by six central and overarching themes: (i) lack of knowledge about autism, (ii) a need for increased participation/involvement, (iii) consideration of autism-specific needs in treatment, (iv) lack of services, (v) limited access to services, and (vi) improvement of stakeholder collaboration. Themes were similarly reported across participants, emphasizing dissatisfaction in all stakeholders. Conclusions We identified major barriers to mental healthcare for autistic adults in Germany that affect autistic adults, but are also of concern to relatives and healthcare providers. Our results point to specific and generic areas for improvement, independent of stakeholder perspectives, which could guide future development of needs- and evidence-based services, recommendations and guidelines of mental healthcare for people with autism across the lifespan. Trial registration This study protocol was preregistered at the Open Science Framework ( https://osf.io/5x8pg ).